2023
DOI: 10.1128/iai.00460-22
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Fibronectin-Binding Proteins Contribute to Colonization of the Female Reproductive Tract

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is an opportunistic pathogen and frequent colonizer of human skin and mucosal membranes, including the vagina, with vaginal colonization reaching nearly 25% in some pregnant populations. MRSA vaginal colonization can lead to aerobic vaginitis (AV), and during pregnancy, bacterial ascension into the upper reproductive tract can lead to adverse birth outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 101 publications
1
1
0
Order By: Relevance
“…A denser, layered Fn fibril network at the surface of osteoblasts demonstrated a poorer uptake of bacteria compared to a moderate Fn fibril network at the surface of A549 epithelial cells suggesting that an optimal concentration and organization of Fn is required for efficient adhesion and uptake. Furthermore, and also in agreement with our results, a recent study has demonstrated that anti-α5β1 antibodies demonstrate no effect on staphylococcal adhesion but abrogate internalization ( 53 ). We, therefore, suggest that clustering of SDC-1 by CD9 and the resulting Fn fibril formation drives the initial adherence of S. aureus .…”
Section: Discussionsupporting
confidence: 93%
“…A denser, layered Fn fibril network at the surface of osteoblasts demonstrated a poorer uptake of bacteria compared to a moderate Fn fibril network at the surface of A549 epithelial cells suggesting that an optimal concentration and organization of Fn is required for efficient adhesion and uptake. Furthermore, and also in agreement with our results, a recent study has demonstrated that anti-α5β1 antibodies demonstrate no effect on staphylococcal adhesion but abrogate internalization ( 53 ). We, therefore, suggest that clustering of SDC-1 by CD9 and the resulting Fn fibril formation drives the initial adherence of S. aureus .…”
Section: Discussionsupporting
confidence: 93%
“…Staphylococcus aureus (S. aureus) is a major bacterium responsible for nosocomial and community-acquired infections in humans, and these infections have persisted despite widespread prevention interventions (Becker and Bubeck Wardenburg 2015;Kadariya et al 2014;Linzner et al 2021). In addition to an increase in S. aureus infections in pregnant and postpartum women, as well as outbreaks in newborn nurseries, there have been reports of S. aureus colonization of the female vaginal tract (Deng et al 2019;Lyon et al 2023). S. aureus can produce toxins under various environmental conditions and can cause a variety of diseases, ranging from minor infections of the epidermis and soft tissues to life-threatening illnesses (Chen et al 2022;Gherardi 2023).…”
Section: Introductionmentioning
confidence: 99%